Book review: Ward, A. (2014). Leadership in residential child care: A relationship–based approach. Norwich: The Smokehouse Press. 184pp. ISBN 9780957633537 - Nigel Horner (Scottish Journal of Residential Child Care)
This delightfully candid book, drawing upon the full length of the author's extensive experience over five decades of working with, researching, and writing about children and young people in residential group care settings, exemplifies the value of understanding our historic present. As Olive Stevenson (1998, p. 154) so aptly observed: 'British child welfare has suffered from a lack of historical reflection: to acknowledge the distinctive and unique problems that we face today does not invalidate comparisons with the past'. If you are looking for an incisive, insightful, restorative text to begin to address this perceived deficit in your understanding of how practice wisdom can be accrued through time, then you can do no better than starting with Adrian Ward's considered reflections.